The Effect of Digital Marketing-Upgrading and Product Virality on the Sustainability of MSMEs - Habibie, Samas Adimisa Mishbah; Santoso, Ribut; Islamudin, Ardhi; Vizandra, Ellyzabeth Putri (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study aims to understand the role of consumer behavior in mediating the influence of virality, digital marketing, and product enhancement on the desires of MSMEs in East Java. This study expands our understanding of the impact of digital marketing, product enhancement, and virality on the desires of MSMEs in East Java, focusing on diverse consumer behavior. With a quantitative approach, this study uses a survey method with a questionnaire as the main instrument, involving 160 respondents from various cities in East Java, including Surabaya, Malang, and Mojokerto. The variables explained include digital marketing (X1) consisting of social media indicators, websites, and mobile marketing; product enhancement (X2) such as product quality and innovation; and virality (X3) which includes content creativity and the use of influencers. Consumer behavior (Y) focuses on satisfaction, loyalty, and interest, as well as MSME desires (Z) which are measured through profitability and public acceptance. The results of the analysis show that digital marketing has a positive effect on consumer behavior, which has an impact on increasing customer loyalty and satisfaction. In addition, product enhancement and virality significantly affect the desire of MSMEs, with consumers more interested in modern and popular products.